Gut Microbiota-Mediated Elevated Production of Secondary Bile Acids in Chronic Unpredictable Mild Stress - Qu, Yuchen; Su, Cunjin; Zhao, Qinhong; Shi, Aiming; Zhao, Fenglun; Tang, Liuxing; Xu, Delai; Xiang, Zheng; Wang, Yang; Wang, Yueyuan; Pan, Jie; Yu, Yunli (Frontiers in Pharmacology, 2022)
A growing body of evidence suggests that gut microbiota could participate in the progression of depression via the microbiota–gut–brain axis. However, the detailed microbial metabolic profile changes in the progression of depression is still not fully elucidated. In this study, a liquid chromatography coupled to mass spectrometry-based untargeted serum high-throughput metabolomics method was first performed to screen for potential biomarkers in depressive-like state a chronic unpredictable mild stress (CUMS)-induced mouse model. Our results identified that the bile acid and energy metabolism pathways were significantly affected in CUMS progression. The detailed bile acid profiles were subsequently quantified in the serum, liver, and feces. The results showed that CUMS significantly promoted the deconjugation of conjugated bile acid and secondary bile acid biosynthesis. Furthermore, 16S rRNA gene sequencing revealed that the increased secondary bile acid levels in the feces positively correlated with Ruminococcaceae_UCG-010, Ruminococcus, and Clostridia_UCG-014 abundance. Taken together, our study suggested that changes in family Ruminococcaceae abundance following chronic stress increased biosynthesis of secondary bile acid DCA in the intestine. Aberrant activation of secondary bile acid biosynthesis pathway thereby increased the hydrophobicity of the bile acid pool, which might in turn promote metabolic disturbances and disease progression in CUMS mice.